1997
DOI: 10.26719/1997.3.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational film on the Health Belief Model and breast self-examination practice

Abstract: A longitudinal study of four phases was conducted to identify the effect of an educational film on the Health Belief Model and breast self-examination practice of second-year nursing students in Alexandria University. Findings showed that the health belief parameters [perceived susceptibility to breast cancer, benefits of and barriers to practising breast self-examination] were influenced differently by the film. A positive influence was observed between breast self-examination practice and film viewing;one-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Our study indicated that women had an increased level of perceived susceptibility following the completion of the BCAC-BC campaign. A similar health belief change was observed for female students in a study conducted in Egypt after an educational video intervention [35], though not in a study of female teachers in northern Turkey, in which women's perceived susceptibility to breast cancer appeared to decrease after a video intervention (8.29 ± 1.83 vs. 7.48 ± 1.78) [17]. It is important that cancer-awareness-raising programs appropriately raise the level of susceptibility in terms of improving awareness about BC risk while guarding against making women feel fearful or apprehensive about their breast health.…”
Section: Discussionsupporting
confidence: 75%
“…Our study indicated that women had an increased level of perceived susceptibility following the completion of the BCAC-BC campaign. A similar health belief change was observed for female students in a study conducted in Egypt after an educational video intervention [35], though not in a study of female teachers in northern Turkey, in which women's perceived susceptibility to breast cancer appeared to decrease after a video intervention (8.29 ± 1.83 vs. 7.48 ± 1.78) [17]. It is important that cancer-awareness-raising programs appropriately raise the level of susceptibility in terms of improving awareness about BC risk while guarding against making women feel fearful or apprehensive about their breast health.…”
Section: Discussionsupporting
confidence: 75%
“…51 There was a positive association between self-breast examination and the use of an HBM based educational film conducted in Egypt. 52 Almost the same result had been found in the study conducted for self-care practice for type II diabetes after implementing HBM-based interventions. 53 It is claimed that HBM is a behaviour change technique rather than a theoretical approach after a systematic review showed controversial findings of the association between HBM components and its relation to behaviour change.…”
Section: Discussionsupporting
confidence: 67%
“…The value of heightened awareness is based on the value of earlier treatment of both nonpalpable and palpable breast cancers. [7,8] There are no data from Libya on women's awareness of breast cancer in general and BSE in particular. Therefore, this study aims to identify the gaps in the knowledge, attitude, and practices of Libyan females with view to guide health education and care.…”
mentioning
confidence: 99%